Examining the aspects of institution choice in connection with the internationalization of higher education - Janik, Henrietta; Naár-Tóth, Zsuzsanna; Vinogradov, Szergej (Decision Making: Applications in Management and Engineering, 2023)
International student mobility is increasing and transforming the image of higher education institutions. This study examines the factors that motivate international students in choosing a destination country. The aspects of the institution selection were examined using a non-parametric test, factor analysis and principal component analysis based on a sample of 270 people. Relying on the results of the research conducted in Hungary, the paper examines the factors influencing the selection of the destination country and further research examining the elements effecting the selection of the final host institution. Based on these results, the study disputes that economic and social impulses within the country of origin serve to “push” students abroad. However, the decision of which destination country to choose depends on several “pull” factors. The study features the usefulness of the quality of human environment, geographic proximity, tuition and living costs, scholarship opportunities, job opportunities after graduation, and the reputation of the destination country or institution, as well as the impact of linguistic proximity on student flow. The present empirical research reveals the close relationships between some pull factors, such as favourable geographical location, institutional support, the quality of the human environment, the expected balanced work environment after graduation, and the country of origin of international students. The results of the factor analysis confirm the underlying structure of the learning variables used in this research and provide empirical support for its application in future studies of international students’ higher education study experiences.